The Relationship Between Self-Esteem and Loneliness in Migrant Students - Lindah, Nur Eva; Nur, Haerani; Ansar, Wilda (Polteknik Ilmu Pemasyarakatan, 2024)
Migrant students who experience a transition to a new environment will face various anxieties while overseas, one of which is the emergence of feelings of loneliness. This research aims to determine the relationship between self-esteem and loneliness in migrant students. The subjects in this research were 276 migrant students studying in the city of Makassar. The sampling technique used was incidental sampling technique. This research uses the Spearman Rho correlation analysis technique. The results of data analysis obtained a significance value (p = 0.001 < 0.005) with a correlation coefficient value (r = -0.546). The results of the analysis show that there is a negative relationship between self-esteem and loneliness in migrant students. The higher the self-esteem, the lower the equality for migrant students, conversely, the lower the self-esteem, the higher the equality for migrant students. This research can provide a basis for the development of psychological intervention programs aimed at increasing self-esteem and reducing levels of loneliness in migrant students.